A study on the factors of stress among secondary school teachers in Melaka Tengah / Ahmad Safwan Hamsi and Ahmad Syahir Muhd Asri Veraiyah - Hamsi, Ahmad Safwan; Muhd Asri Veraiyah, Ahmad Syahir (Faculty of Administrative Science and Policy Studies, 2013)
The purpose of this study is to identify the level of stress and the factors that influenced to the stress among secondary school’s teachers. 308 teachers in Melaka Tengah have been chosen as the respondents. The aspects that to be identified were workload, involvement of parent and students’ behaviour. The instrument of this study is questionnaire form. Sampling has been done by multiple stage cluster sampling. The data was analyzed using Statistical Package for Social Science (SPSS) for Windows. Descriptive statistic in terms of frequency is used to analyze the level of stress. The inference statistic that is Pearson correlation and regression analysis are used to test the hypothesis. Results showed that the level of stress among secondary school’s teachers were in medium level. The results also showed that there were no significant relation between the amount of workload factor and the level of stress. Furthermore, there were significant relation between involvement of parent and students’ behaviour with the level of stress among the teachers. The most dominant stress’ factor was student’s behavior.